High pressure CO2 absorption from natural gas using piperazine promoted 2-amino-2-methyl-1-propanol in a packed absorption column - Halim, H.N.A. (Elsevier B.V., 2015)
Monoethanolamine (MEA) is the most established solvent used in CO2 absorption studies at low-pressure conditions. However, it has several limitations, such as a low CO2 loading capacity, high degradation, and a tendency to corrode processing equipment. Therefore, this study reports the absorption performance of an alternative absorbent: the Piperazine (PZ) promoted 2-Amino-2-Methyl-1-Propanol (AMP) blended solvent for use in the removal of CO2 from natural gas (NG) in high pressure conditions. The performance of the PZ + AMP blended solvent was compared with the MEA solvent according to various operating pressures (0.1-4.0 MPa), in percentage terms of CO2 removal efficiency, as well as the overall volumetric mass transfer coefficient for the gas phase based on unit mol fraction driving force (Kyav). The absorption experiments were conducted in an absorption column packed with Sulzer metal gauze packing for the effects of total gas flow rate (33-51 kmol/m2 h), liquid flow rate (2.89-3.97 m3/m2 h), MEA concentration (20-40 wt) and liquid temperature (30-45 Â°C). From this study, the Kyav value of the 7 wt PZ + 23 wt AMP blended solvent was higher than the value for 30 wt MEA solvent. Nonetheless, the Kyav values for both solvents increased from a rising operating pressure, most notably at operating pressures greater than 2.0 MPa. Â© 2015 Elsevier B.V. All rights reserved.